Exploring the unknown: electrophysiological and behavioural measures of visuospatial learning. (16th March 2016) - Quinlivan, Brendan; Butler, John S.; Ridwan, Abdur Raquib; Beiser, Ines; Williams, Laura; McGovern, Eavan; O'Riordan, Sean; Hutchinson, Michael; Reilly, Richard B.
Abstract: Visuospatial memory describes our ability to temporarily store and manipulate visual and spatial information and is employed for a wide variety of complex cognitive tasks. Here, a visuospatial learning task requiring fine motor control is employed to investigate visuospatial learning in a group of typically developing adults. Electrophysiological and behavioural data are collected during a target location task under two experimental conditions: Target Learning and Target Cued. Movement times (MTs) are employed as a behavioural metric of performance, while dynamic P3b amplitudes and power in the alpha band (approximately 10 Hz) are explored as electrophysiological metrics during visuospatial learning. Results demonstrate that task performance, as measured by MT, is highly correlated with P3b amplitude and alpha power at a consecutive trial level (trials 1–30). The current set of results, in conjunction with the existing literature, suggests that changes in P3b amplitude and alpha power could correspond to different aspects of the learning process. Here it is hypothesized that changes in P3b correspond to a diminishing inter‐stimulus interval and reduced stimulus relevance, while the corresponding changes in alpha power represent an automation of response as habituation occurs in participants. The novel analysis presented in the current study demonstrates how gradual electrophysiological changes can be tracked during the visuospatial learning process under the current paradigm. Abstract : The current study is an investigation into electrophysiological and behavioral metrics during a visuospatial learning paradigm. P3b amplitudes during the learning process were examined and found to decrease with learning. Alpha power was also investigated and was found to increase during the learning process. Here we argue that the decrease in P3b amplitude is primarily related to a decreasing inter‐stimulus interval while the increase in alpha power relates to habituation of response and a decreased attentional load during the learning process.